2020
DOI: 10.1109/access.2020.3012689
|View full text |Cite
|
Sign up to set email alerts
|

Taxi High-Income Region Recommendation and Spatial Correlation Analysis

Abstract: Taxis provide essential transport services in urban areas. In the taxi industry, the income level remains a cause of concern for taxi drivers as well as regulators. Analyzing the variation trend of taxi operation efficiency indicators throughout the day, mining high-income order hot-spots and high-income regions at different periods, will effectively improve the average hourly incomes (AHI) of drivers. This paper selects the order data for each day of holidays, working days, and non-working days through the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…With the application of big data in the transportation field, taxi GPS data is used to analyze the spatiotemporal distribution characteristics of taxi operation [2] , identify urban functional areas [3] , analyze pick-up and drop-off hotspots [4] , predicting travel demands [5] , and more. Previous studies have shown that pick-up and drop-off hotspots do not necessarily overlap with high-income order areas [6] . Therefore, to help drivers select high-earnings orders accurately, we need to analyze the spatial distribution of earnings and identify high-earnings order areas.…”
Section: Introductionmentioning
confidence: 92%
“…With the application of big data in the transportation field, taxi GPS data is used to analyze the spatiotemporal distribution characteristics of taxi operation [2] , identify urban functional areas [3] , analyze pick-up and drop-off hotspots [4] , predicting travel demands [5] , and more. Previous studies have shown that pick-up and drop-off hotspots do not necessarily overlap with high-income order areas [6] . Therefore, to help drivers select high-earnings orders accurately, we need to analyze the spatial distribution of earnings and identify high-earnings order areas.…”
Section: Introductionmentioning
confidence: 92%
“…The Thiessen polygon method for separating plots was originally used by discrete weather stations to calculate rainfall [33]. It was also used to analyze urban non-physical elements, such as real estate prices and cab fares in different areas of the city [34,35]. The assessment model in this study, which is proposed for historic districts, focuses on the history and culture of non-physical elements.…”
mentioning
confidence: 99%